A healthier workplace? Implementation of fruit boxes in the workplace - Pescud, M.; Waterworth, P.; Shilton, T.; Teal, R.; Slevin, Terry; Ledger, M.; Lester, L.; Rosenberg, M. (Sage Publications, 2016)
© The Authors 2016 .Objective: The purpose of this study was to investigate whether making fruit boxes available in the workplace is a successful health promotion strategy. Design: A quasi-experimental study involving three conditions - free fruit, 50c per piece of fruit and $1 per piece of fruit - to investigate the effect of a contribution scheme on employees' fruit purchase/consumption behaviours and willingness to contribute when in the paid conditions. Setting: Perth, Western Australia. Methods: In total, 36 workplaces participated and were randomly assigned to one of the three conditions. The results were analysed using generalised linear modelling. A qualitative follow-up was conducted with workplace representatives 6 weeks after the completion of the trial to investigate how many workplaces implemented the provision of fruit boxes after the trial and the factors influencing the decision to implement fruit boxes. Results: A significant difference in average fruit purchasing/consumption per person was found with respect to condition (p <.001), with businesses in the free condition purchasing/consuming a significantly greater amount of fruit than businesses in the 50c contribution condition or $1 contribution condition. Following the trial, 13 workplaces continued providing their own fruit box, of which 7 were initially in the free condition. Qualitative findings revealed that management support, a receptive culture and sufficient resources were key to the implementation of fruit boxes. Conclusion: Having a fruit box may be a feasible health promotion strategy, and the financial burden of this strategy could be alleviated by asking employees to contribute to the cost of fruit.